Fungsi Uslūb al-Qashr sebagai Penegasan Makna - Nur Amirah Rifkah; Mohamad Harjum; Fatkhul Ulum (PT. Saha Kreasi Indonesia, 2026)
The science of balaghah has an important role in understanding the beauty and accuracy of the meaning of the Arabic language, especially through the study of 'ilm al-ma'ani. One of the main discussions in this branch is uslūb al-qashr, which is a language style that functions to limit and affirm meaning through certain specializations. The study of qashr is important because this language style is widely used in Arabic texts, especially Al-Qur'an, to strengthen meaning and straighten understanding. This research aims to describe the concept of qashr systematically, including the meaning, elements, division, and customs or language tools used in its formation. The research method used is qualitative-descriptive with a literature study approach to classical and contemporary balaghah literature. Research results show that qashr functions as an effective rhetorical tool in affirming the meaning through the restriction of nature or maushuf, both in essence and idhafi. Qashr is divided into qashr haqiqi and qashr idhafi which includes qashr ifrad, qashr qalb, and qashr ta'yīn, and is realized through several qashr customs such as nafy wa istitsnā', lafaz innamā, the use of the letter 'athaf, and the introduction of sentence elements. The conclusion of this study confirms that the understanding of uslūb al-qashr is very important in the analysis of Arabic texts because it contributes greatly to the affirmation of the meaning and rhetorical power of language.